Catalysis: The Technology Enabler for New, Low Carbon Energy Technologies. Issue 9 (10th May 2017) - Huber, George W.; Bond, Jesse Q.
Abstract : Good catalysis for great energy ! Sustainably providing the world with clean, reliable, and cost‐effective energy is one of the most substantial challenges facing modern society. Catalysis science is central to realizing this vision. This special issue samples a diverse set of catalysis sub‐disciplines to highlight recent, cross‐cutting advances within the broad field of energy technology.